Species of the Polistes (Polistella) (Hymenoptera: Vespidae: Polistinae) from Vietnam, with description of a new species and a pictorial key - Nguyen, Lien T.p.; Nguyen, Cuong Q.; Bozdoğan, Hakan (Zootaxa, 2018)
Twenty seven species of the subgenus Polistella Ashmead, 1904 are recorded from Vietnam. Polistes chuyangsin Nguyen & Nguyen sp. nov. and its nest are described and figured. A pictorial key to Vietnamese species of the subgenus is provided.